La guerre de Troie, matrice de la guerre de croisade - Florence Tanniou (Astérion)
Throughout the Middle Ages, the Trojan legend was used as a benchmark for writing about war. But, it was in the backdrop of the Crusades, in particular the Fourth Crusade (1204) and its aftermath, that it becomes a fully significant archetype. On the one hand, the Trojan War featured in the narrative of contemporary conflicts and, on the other hand, the Trojan narrative was expanded on and updated, so as to express and reflect on ongoing conflicts. Through a distinct geographical overlap between Troy and Constantinople, the ongoing war is portrayed in the way it coincides with the very locations of the past conflict, generating a reflection on the causes of the war that offers a cyclical vision of time and calls for stratigraphical comprehension. These textual and iconographic resonances between Troy and the Crusade shape questions and uncertainties about war and make the myth a matrix that is poetic , historical and political.